Detection of Amitraz Resistance in Rhipicephalus (Boophilus) microplus from SBS Nagar, Punjab, India. (10th February 2014) - Singh, N. K.; Nandi, Abhijit; Jyoti,; Rath, S. S.
Abstract : The resistance status of Rhipicephalus (Boophilus) microplus collected from SBS Nagar, Punjab, was evaluated against amitraz by Adult Immersion Test (AIT). The regression graph of probit mortality of ticks plotted against log values of progressively increasing concentrations of amitraz revealed the slope of mortality (95% CI) as 2.36 ± 0.61 (0.38 to 4.33). The LC50 (95% CI) and LC95 (95% CI) values were recorded as 332.52 ppm (305.06–362.44) and 1646.93 ppm (1383.97–1959.84), respectively, and the resistance factor (RF) was 13.17 which indicated level II resistance status. The dose response curves for egg mass weight, reproductive index, and percentage inhibition of oviposition were also validated by AIT and the slopes (95% CI) were - 7.17 ± 2.41 (−14.85 to 0.50), - 0.009 ± 0.02 (−0.16 to −0.031), and 19.99 ± 4.77 (4.81 to 35.17), respectively. The current study reports the development of resistance in R. (B.) microplus to amitraz from Punjab state and the data generated would be useful in formulation of effective control strategies against ticks of this region.